The frequency of human papilloma virus types 16, 18 in upper genital tract of women at high risk of developing ovarian cancer - Bilyk, O.O.; Pande, N.T.; Pejovic, T.; Buchynska, L.G. (Experimental Oncology, 2014)
Aim: To investigate the incidence of human papilloma virus (HPV) types 16, 18 in upper genital tract of women considered at a high risk (HR) of developing epithelial ovarian cancer (EOC). Methods: HPV 16 and 18 E6 ORF specific semiquantitative PCR was used to screen the incidence of HPV in 20 women at HR of developing EOC and 10 women with no ovarian disease (control). Results: The HR subset of fallopian tubes and ovarian tissues showed greater positivity for HPV E6 ORF (40%) as compared to control (10%) tissues. Of all the samples, two (10%) were positive for HPV 16, two (10%) were positive for HPV 18, and four (20%) showed positivity for mixed HPV 16/18 infection. The presence of HPV E6 ORF was found both in the fallopian tubes and ovarian DNA from 6 (30%) patients. In two cases (10%) we detected HPV ORF only in the fallopian tube derived genomic DNA. Conclusion: It has been shown the presence of HPV in the upper genital tract in women at HR of developing EOC in close proximity of HPV susceptible tissue cervix. Key Words: HPV, high risk of ovarian cancer.